Statutory Protection for Renters: Classification of State Landlord–Tenant Policy Approaches. Issue 1 (2nd January 2017) - Hatch, Megan E.
Abstract: There are many federal, state, and local laws governing the landlord–tenant relationship. Yet scholars know little about their variety and what impact differences among jurisdictions have on renters and rental housing markets. This article examines state-level landlord–tenant policy approaches to determine whether there is significant policy variation and whether states illustrate identifiable policy types. Using cluster and discriminant analysis, this research creates a typology of landlord–tenant policy approaches, finding three distinctive approaches: protectionist, probusiness, and contradictory . This research indicates there is significant variation among state landlord–tenant statutory policies, although states' laws generally reflect one of three philosophies. These results are important for future studies on rental housing because treating all state rental environments the same masks important differences in rental experiences across states. As an illustration, this article finds that renters in protectionist and contradictory states move significantly more than renters in probusiness states do. Furthermore, understanding where renters have more or less legal protection allows policymakers and advocates to focus their efforts on areas where assistance is most needed.